Functionalized glycolipids for potential bioconjugation of vesicles - Tabandeh, Mojtaba; Goh, Ean Wai; Salman, Abbas Abdulameer; Heidelberg, Thorsten; Hussen, Rusnah Syahila Duali (Elsevier, 2018)
Two azide-terminated oligoethylene oxide spacered glycolipids have been synthesized, and their assembly behavior has been studied in comparison to the corresponding base surfactants. The results suggest potential of the Guerbet lactoside-based compound for targeted drug delivery, while a coiling of the ethylene oxide linker disfavors the application of the glucoside.